Endoscopic repair of recurrent congenital H-Type tracheoesophageal fistula with electrocautery and tissue adhesive : a case report with endoscopic pictures to illustrate technique - Kevin Boon Han, Ng; Thambidorai R., Rao; Fadhli, Mohamed Sani; Jeyanthi, Kulasegarah (The University of Toronto Medical Journal (UTMJ), 2022)
The recurrence of a tracheoesophageal fistula (TOF) is a known complication that follows a primary operative repair of a TOF. It is a diagnostic and therapeutic challenge due to its significant morbidity. Treatment options include open surgical repair or endoscopic repair of the fistula. We present a case of a recurrent TOF in an 11-month-old girl with tetralogy of fallot that was treated successfully via endoscopic approach with electrocautery and tissue adhesive.